The effects of wearing high heeled shoes on the muscles and joints of lower limb - Polat Sema; Kabakcı Ayşe Gül (Sciendo, 2021)
Study aim: The aim of this study is to investigate whether the lower extremity muscles' force/torque/strength and range of motion may be affected in females wearing high heeled shoes and not wearing high heeled shoes.